Osteopontin - The stirring multifunctional regulatory factor in multisystem aging - Du, Yuxiang; Mao, Liwei; Wang, Zhikun; Yan, Kai; Zhang, Lingli; Zou, Jun (Frontiers in Endocrinology, 2022)
Osteopontin (OPN) is a multifunctional noncollagenous matrix phosphoprotein that is expressed both intracellularly and extracellularly in various tissues. As a growth regulatory protein and proinflammatory immunochemokine, OPN is involved in the pathological processes of many diseases. Recent studies have found that OPN is widely involved in the aging processes of multiple organs and tissues, such as T-cell senescence, atherosclerosis, skeletal muscle regeneration, osteoporosis, neurodegenerative changes, hematopoietic stem cell reconstruction, and retinal aging. However, the regulatory roles and mechanisms of OPN in the aging process of different tissues are not uniform, and OPN even has diverse roles in different developmental stages of the same tissue, generating uncertainty for the future study and utilization of OPN. In this review, we will summarize the regulatory role and molecular mechanism of OPN in different tissues and cells, such as the musculoskeletal system, central nervous system, cardiovascular system, liver, and eye, during senescence. We believe that a better understanding of the mechanism of OPN in the aging process will help us develop targeted and comprehensive therapeutic strategies to fight the spread of age-related diseases.